Prevalence of hypertension and prehypertension among a coastal population in south India: baseline findings from a population-based health registry project in Kerala. (February 2018) - Anand, T.N.; Shaffi, M.; Pillai A, M.; Lathika Rajendrakumar, A.; Sreemathy, L.S.; Rajasekharan Nayar, K.; Lordson, J.; Abraham, M.; Rajeev, P.; Marthanda Pillai, A.; Kumar, A.; Grace A, C.; et al.
Highlights: Study reports higher prevalence of hypertension (above 50%) and prehypertension (above 30%) in coastal Kerala. According to our knowledge, this is the first large study reporting hypertension and prehypertension prevalence in coastal Kerala. Study reports higher prevalence of hypertension (above 50%) and prehypertension (above 30%) in coastal Kerala compared with previous studies.